Synthesis and characterization of microwave assisted acetylated rice starch / polyethylene oxide (PEO) blends - Ong, Kai Sin (2024)
Rice starch was modified via microwave-assisted esterification using acetic anhydride in the presence of iodine as the catalyst. An analysis of infrared spectra using Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy showed a prominent peak at 1732 cm-1, indicating the successful acetylation of rice starch due to the presence of the carbonyl (C=O) group. The impact of the molar ratio of rice starch to acetic anhydride, the amount of iodine, and the reaction time on the degree of substitution (DS) of acetylated rice starch were investigated. The highest DS was achieved with a molar ratio of 1:4, using 0.25 mmol of iodine and a reaction time of two minutes. Solution casting was used to prepare polymer blends of poly(ethylene oxide) (PEO) with acetylated rice starch in various ratios. Differential scanning calorimetry (DSC) was utilized to investigate the isothermal crystallization, melting behavior, and miscibility of PEO in PEO/acetylated rice starch blends. The kinetics of isothermal crystallization of PEO in PEO/acetylated rice starch blends were analyzed using the Avrami equation. The Hoffman-Weeks equation was used to estimate the equilibrium melting temperatures, Tm° of PEO and PEO/acetylated rice starch blends. The Nishi-Wang equation was used to investigate the miscibility of PEO and acetylated rice starch. Positive values of polymer-polymer interaction parameter, 12 for the PEO/acetylated rice starch blends were obtained, indicating that the blends were immiscible.